UPAYA MENINGKATKAN HASIL BELAJAR NILAI-NILAI PANCASILA MELALUI DISKUSI KELOMPOK PADA PESERTA DIDIK KELAS 3 SDN 15 KOTO BARU. - Dewon Ira novota safitri, resha albadri, wiwin ayunda (Jurnal Dharma PGSD, 2025)
Abstract: The purpose of this study is to improve This study improves the learning achievement of grade 3 students of SDN 15 Koto Baru in understanding the values ​​of Pancasila through the application of group learning methods. The research method used is Classroom Action Research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 30 grade 3 students. The results of the study showed a significant increase in student learning outcomes with an average score increasing from 65 in cycle I to 85 in cycle II. The application of the group method showed effectiveness in improving the understanding and practice of Pancasila values ​​among students.